Perspectives in waging conflicts constructively cases, concepts, and practice - Dayton, Bruce W.; Kriesberg, Louis (Rowman & Littlefield, 2017)
This book explores how large-scale conflicts can be waged more constructively. An introduction presents key concepts in positive conflict resolution, and chapters from esteemed contributors illustrate these theories in action, with cases ranging from Israel to North Korea. The book offers diverse perspectives and concrete ideas for positive change.